CBR test on fibre reinforced silty sand - Chegenizadeh, A; Nikraz, Hamid (IJSCE, 2012)
Geosynthetic fibres are an established family of geomaterials used in a wide variety of civil engineering applications such as pavement systems. In pavement design, CBR ratio count as an important parameter. This study aims to investigate effect of fibre inclusion on CBR ratio. A series of laboratory investigation were carried out to evaluate effects of reinforcing the sub grade soil in pavement system with randomly distributed plastic fibres. In this study, one type of soil (i.e silty sand) and two type of fibre were used. CBR test were conducted on unreinforced samples as well as reinforced ones at different fibre contents (i.e. 0.1%, 0.3%) and different fibre length (i.e. 10mm , 20 mm and 40mm).The results of CBR test showed that the CBR ratio for reinforced silty sand increased even more than two times in some cases as fibre content and fibre length increased. The results proved that application of short randomly distributed fibre is a good method to apply in practical projects.